Reactivation of forgotten spaces: Proposal to transform the Quebrada Pedregal into a public space vital for Tumbes - La Rosa-Boggio, Diego Orlando; Torres Samillán, Rosa Amelia; Escobar Carreño, Abner Josue; More Ayala, Samantha Aymee; Castellano Arellano, Pamela del Carmen; Zulueta Cueva, Carlos Eduardo; Arevalo García, Analía (LACCEI, 2025)
The research focused on the remaining spaces in the city of Tumbes, Peru, which are forgotten and problematic areas and can become an opportunity to transform them into places that are pleasant for the population. The general objective was to determine the public perception of pollution in these areas and their attitude towards a proposal for recovery, whose main strategy was to articulate the shores and give recreational use to the population. A quantitative and descriptive research was carried out, using the survey of population over 15 years old as an instrument. The results show that most are aware of the high level of pollution and agree to maintain and care for the new public space.